Modulation above Pump Beam Energy in Photoreflectance. (9th July 2017) - Fuertes Marrón, D.
Abstract : Photoreflectance is used for the characterisation of semiconductor samples, usually by sweeping the monochromatized probe beam within the energy range comprised between the highest value set up by the pump beam and the lowest absorption threshold of the sample. There is, however, no fundamental upper limit for the probe beam other than the limited spectral content of the source and the responsivity of the detector. As long as the modulation mechanism behind photoreflectance does affect the complete electronic structure of the material under study, sweeping the probe beam towards higher energies from that of the pump source is equally effective in order to probe high-energy critical points. This fact, up to now largely overseen, is shown experimentally in this work. E 1 and E 0   +  Δ0 critical points of bulk GaAs are unambiguously resolved using pump light of lower energy. This type of upstream modulation may widen further applications of the technique.